2005
DOI: 10.1038/ng1510
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping for hypertension loci with genome-scan markers

Abstract: Identification of genetic variants that contribute to risk of hypertension is challenging. As a complement to linkage and candidate gene association studies, we carried out admixture mapping using genome-scan microsatellite markers among the African American participants in the US National Heart, Lung, and Blood Institute's Family Blood Pressure Program. This population was assumed to have experienced recent admixture from ancestral groups originating in Africa and Europe. We used a set of unrelated individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
225
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(243 citation statements)
references
References 21 publications
12
225
2
4
Order By: Relevance
“…[2][3][4] Previous studies have also suggested that AFR admixture in AFA was associated with hypertension but either failed to reach statistical significance or showed only a modest effect. [6][7][8] This study shows statistically significant association of AFR admixture and hypertension in both AFA and HA population groups. Our study differs from previous studies with respect to having a much larger sample size and that our participants were restricted to adult post-menopausal women.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…[2][3][4] Previous studies have also suggested that AFR admixture in AFA was associated with hypertension but either failed to reach statistical significance or showed only a modest effect. [6][7][8] This study shows statistically significant association of AFR admixture and hypertension in both AFA and HA population groups. Our study differs from previous studies with respect to having a much larger sample size and that our participants were restricted to adult post-menopausal women.…”
Section: Discussionmentioning
confidence: 53%
“…[2][3][4] A potential contributing factor to the differences in prevalence of hypertension may be the degree of admixture within individuals residing in the United States, a highly heterogeneous genetic population. Previous studies have either not shown a statistically significant difference in African admixture within AFA subjects with and without hypertension 6,7 or have shown modest differences. 8 Although one group found hypertension association with specific African inherited chromosomal regions 6 these findings have not been supported by other studies.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Measures of excess admixture form the basis for mapping phenotypic variation and loci that contribute to isolation between taxa [4,28], although different implementations of admixture mapping parameterize and utilize excess admixture in different ways. http://doc.rero.ch 2 mapping incorporates population structure through its measure of excess ancestry (Box 1).…”
Section: Glossarymentioning
confidence: 99%
“…http://doc.rero.ch [27][28][29][30][31]. However, multiple studies have identified genetic variants associated with lighter and darker skin pigmentation in humans [32][33][34], a trait that might be differentially selected in regions with low and high ultraviolet radiation (UVR), owing to known associations between skin pigmentation and vitamin D synthesis and protection from UVR [34,35].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 99%